Das sobras à indústria da reciclagem: a invenção do lixo na cidade - Uberlândia-MG 1980-2002 - Couto, Ana Mágna Silva (2006)
This researchs sought problemas of relationship of living around the trash, in the city of Uberlandia-MG, for the years of 1980 thru 2002. The question of the trash constituted complex and vast matter. As problematics of the space and of live urban, of trash can be learned, between other things, as empreendiment /negotiate, work/survive and as well in what refers, to the municipal government, problem of the administration public and of the political. We proposed ourselves to deal with trash as object of analyzes history, social problem and political, new way to Work and to survive, factor with implication strainght the life off the people. A document contributed for deciphering some transformation that Itself inscribes In the space possible of to read in the different forms of handles and apropriation of the remainders. Register that will translate lhe way to look at the trash history in that the relationship established with him reveals deep changes in the body of city and in the sensibility of his inhabitantes. In that road, the alternatives and solution that be found for give, a fale to the remainders that the city produces, articulates itself to Institution of the places of trash, contributing for evindential important aspects of the urban life - determined habits of the population and limits of norms and laws, that for times, left of to be observed keeps even by the organizations publics. Upon studing a plan designed by the contradict social,that they contribute for disobey. In a short period of time, a problematic of the trash assumes different dimentions and growing complexity: of a question environmental and of health public to his institutionalization as merchandise. The management of the remainders delineate not barely new instruction of the society, so much social as much as political, like a perception of the exploration of lhe trash and possibility itself to earn profit